Pain intensity and pain unpleasantness in triathletes: A study examining their associations with pain catastrophizing and pain expectations. (July 2021) - Gagnon-Dolbec, Alexis; Fortier, Michelle; Cormier, Stéphanie
Abstract: Objective: Triathletes represent a growing and unique population of individuals willing to endure significant mental and physical stress to practice the sport they love. However, little is known about the pain experienced while training for and competing in a triathlon and how psychological factors influence this experience. This study will assess pain experienced by triathletes in training and competition, and investigate the association between pain catastrophizing and pain expectations with triathlon pain intensity and pain unpleasantness. Design: In this observational study, a sample of 261 triathletes completed two online surveys before and after participating in a triathlon. Results: Moderate levels of pain intensity and pain unpleasantness were reported during training and competition. Pain catastrophizing was positively associated with expected and actual triathlon pain unpleasantness, but not with pain intensity. Expected pain intensity was also significantly associated with pain intensity experienced while competing, whereas expected pain unpleasantness was significantly related to both triathlon pain intensity and unpleasantness. Finally, regression analysis revealed pain catastrophizing and pain expectations to be unique predictors of triathlon pain intensity and pain unpleasantness. Conclusion: This study highlights the important role of psychological factors in triathletes' experience of pain and could eventually help tailor interventions aimed at improving the practice of triathlon. Highlights: Moderate levels of pain intensity and pain unpleasantness are reported by triathletes, both during training and competition. Pain catastrophizing and pain expectations are unique predictors of triathlon pain intensity and pain unpleasantness. Age, gender, distance, and pain at the starting line also predict triathlon pain unpleasantness. Whereas gender and pain at the starting line also contribute to the prediction of triathlon pain intensity. Psychological factors must be considered to improve our understanding of pain experienced by triathletes.